The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40120-021-00241-8
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Experience in Multiple Sclerosis: The Good, the Bad and the Neutral

Abstract: Introduction While the current COVID-19 pandemic has affected the lives of many, there is a paucity of information on the impact on people with multiple sclerosis (MS). This study sought to gain insight into the impact of the current situation on people with MS and the factors that influence this. Methods 324 MS patients participated in this online cross-sectional survey during the COVID-19 lockdown period. A mixed methods design was used, with quantitative information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…It is hypothesized that this may be due to the higher prevalence of mental illness prior to the pandemic among young adults and/or consequences of COVID-19 such as unemployment, the closure of post-secondary educational institutions, and increased social isolation. Our results are in line with other research finding that younger PwMS have been more adversely affected by the COVID-19 pandemic ( Morris-Bankole and Ho, 2021 ; Talaat et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is hypothesized that this may be due to the higher prevalence of mental illness prior to the pandemic among young adults and/or consequences of COVID-19 such as unemployment, the closure of post-secondary educational institutions, and increased social isolation. Our results are in line with other research finding that younger PwMS have been more adversely affected by the COVID-19 pandemic ( Morris-Bankole and Ho, 2021 ; Talaat et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Given the vulnerability to depression and anxiety in this population and the effects of social isolation or loneliness, it was anticipated that we would observe relative increases in depression and anxiety during this time, consistent with other cross-sectional studies that have been published recently. ( Morris-Bankole and Ho, 2021 , Motolese et al, 2020 , Donisi et al, 2021 , Costabile et al, 2021 , Uhr et al, 2021 , Alirezaei et al, 2021 ) When examining the overall rates of depression and anxiety prior to and during the pandemic, we indeed found an increase in the rate of depression from 13% to 29% and an increase in the rate of anxiety from 28% to 47%. Closer examination of the trajectories of depression and anxiety over time, as seen in Table 2 , suggests a combination of both consistency and novelty in mental health symptoms from pre-pandemic status.…”
Section: Discussionmentioning
confidence: 51%
“…The analysis conducted by Forner and colleagues underlined that delays in surgery for cancer patients due to the pandemic resulted in extensive psychosocial distress, and found that patients could mitigate these effects through various coping mechanisms and improved communication with their healthcare teams [15]. Furthermore, the COVID-19 lockdown significantly and negatively impacted younger people with multiple sclerosis (MS), in particular in those with progressive types of MS and psychological symptoms [16]. Nonetheless, as reported by Gleason and colleagues, COVID-19 has disrupted health systems and social services, leading to unprecedented barriers to access and maintain health and addiction services in both inpatient and outpatient settings [17].…”
Section: Discussionmentioning
confidence: 99%